Phycobiliproteins: Recent Developments and Future Applications - Kannaujiya, Vinod K. ; Sundaram, Shanthy ; Sinha, Rajeshwar P. (Springer, 2020)
The biotechnological and industrial signiicance of phycobiliproteins (PBPs) for several commercial applications in the ields of biotechnology, biomedicine, phar- maceuticals, colorants, luorescence agents, and food products is widely known. PBPs are major accessory light-harvesting antenna complexes, which exhibit incredible colors and play a vital role in the harvesting of light energy from the sun. The evolutionary diversity of ancient PBPs among cyanophyta, rodophyta, and cryptophyta facilitates research and development to understand hidden functional aspects of energy utilization. Future research will drive the ield toward greater understanding of PBPs for proper utilization in various applications in biological science, including energy devices. This book encompasses topics of biotechnology, puriication technology, molecular biology, production technology, biochemistry, stress biology, biomedicine, food technology, structural biology, genomics, and pro- teomics of PBPs.